Characterization of atmospheric emission sources of heavy metalsand trace elements through a local-scale monitoringnetwork using T. capillaris - Abril, Gabriela Alejandra (2014)
This research work presents new insights regarding biomonitoring studies, source apportionment at a local scale, and influence of wind and topography on dispersion of atmospheric pollutants in a complex scenario. The monitoring network consisted of transplanted Tillandsia capillaris biomonitors throughout 3 sampling periods in order to assess the effects of the different emission sources and their atmospheric dispersions in a region from the province of Córdoba, Argentina. The elements Mn, Fe, Co, Ni, Cu, Zn, Cd and Pb, were analyzed by Flame Atomic Absorption Spectrometry (FAAS, pseudo-total metal content) and As, Ba, Ca, Ce, Cr, Cs, Eu, Fe, Hf, La, Lu, Na, Rb, Sb, Sc, Se, Sm, Ta, Tb, Th, U, Yb and Zn, by Neutron Activation Analysis (NAA, total metal content). The following atmospheric emission sources were characterized in the study area: cement plant, with emissions of Cd, Pb, CoFAAS, Ni and Ca; waste dumping site fires, with emissions of the elements Sm, Yb, Ba, La, ZnNAA, Ce, Th and Hf; brick kilns with emissions of the elements Na, Ba, As, Se, Cr, Tb, Sc, FeNAA, CoNAA, Ta; vehicular traffic with emissions of ZnFAAS and Sb and soil re-suspension with emissions of Ni, ZnFAAS, Br, U, Mn, Rb and Eu. It was noticeable that topography played an important role in the dispersion of the pollutants in the study area and this was reflected in the biomonitors. Our results provide a step forward in the application field of this biomonitoring species for characterizing emission sources in a complex scenario at a local scale.